'It's all hands-on, even for management': Managerial work in the UK cafe sector. (April 2014) - Lloyd, Caroline; Payne, Jonathan
The growth in managerial jobs is often presented by policy makers as evidence of the UK's success in developing high-skilled, well-paid employment. At the same time, concerns have been raised that the lack of higher level qualifications in the managerial workforce has a detrimental impact on productivity and performance. This article focuses on the relatively neglected figure of the first line manager in private services through a study of the UK cafe sector. It explores the content and quality of the cafe manager's job, and interrogates the purported benefits of upskilling through graduate level qualifications. The findings indicate that these jobs leave much to be desired in terms of pay and work content, and that managers are highly constrained by the degree of centralized control wielded by head office. Limited autonomy and, in many cases, poor job quality raise crucial questions about the ability of lower level managers to influence performance, even allowing for higher level qualifications.